2009
DOI: 10.1111/j.1365-2133.2009.09030.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque thickness and morphology in psoriasis vulgaris associated with therapeutic response

Abstract: Using a patient's baseline plaque morphology to choose a primary treatment modality may result in earlier disease improvement and reduce the cost of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…E Edson-Heredia et al Table S1 online) (Naldi et al, 2008;Rakkhit et al, 2009). We found no evidence to suggest that response to psoriasis therapy might be affected by patient gender (Figure 2).…”
Section: Patient Demographics and Characteristicsmentioning
confidence: 75%
See 2 more Smart Citations
“…E Edson-Heredia et al Table S1 online) (Naldi et al, 2008;Rakkhit et al, 2009). We found no evidence to suggest that response to psoriasis therapy might be affected by patient gender (Figure 2).…”
Section: Patient Demographics and Characteristicsmentioning
confidence: 75%
“…Interestingly, ustekinumab dosing is weight-dependent, whereas dosing of adalimumab is not. Weight loss, used as a surrogate for BMI reduction, was also predictive of improved Randomized controlled trials (n =3) (Gordon et al, 2006a;Menter et al, 2010b;Papp et al, 2008) Pooled analysis of data from clinical trials (n =2) (Gordon et al, 2006b;Reich et al, 2006) Cohort (n =4) (Driessen et al, 2009;Lebwohl et al, 2010;Mazzotta et al, 2009;Naldi et al, 2008) Case series (n =5) (Antoniou et al, 2009;Bardazzi et al, 2010;Duarte and Chehin, 2011;Na et al, 2008;Rakkhit et al, 2009) Open-label extension study (n =1) (Strober et al, 2006) Level 2 (n =4)…”
Section: Patient Demographics and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that in patients with psoriasis the area of disease involvement during stable disease correlates with nail and joint involvement and the need for a second-line therapy (118). Plaque thickness has also been found to correlate with treatment response, where patients with thin plaques were more likely to report a complete clinical response following treatment with topical corticosteroids and phototherapy, but not systemic therapy (119).…”
Section: Patient Selectionmentioning
confidence: 99%
“…In RA, one study showed that when assessed using power Doppler and MRI, 19% of patients thought to be in remission displayed deterioration in radiographic damage (105). Likewise, the inflammatory and epithelial genes that are associated with residual disease genomic profile -or genetic memory -in psoriasis may provide an estimation of subclinical disease activity and probability of relapse with or without treatment; while plaque thickness may provide a good measure of treatment response and the likelihood of a patient responding to treatment (62,119).…”
Section: Assessing the Benefits Of Early Interventionmentioning
confidence: 99%